Quality and economic factors affecting preference for upcycled clothes of selected working women in Metro Manila - Malibiran, Richelle Gwynne D. (College of Home Economics, University of the Philiuppines Diliman, 2010)
ABSTRACT This is a descriptive type of research which aimed to determine the quality and economic factors that affect the preferences of fifty (50) selected working women in the creative field for upcycled clothes. Under quality factors were material selection, design concept, workmanship, fit and comfort, while under economic factors were price, wearability, durability, ease of care, sustainability and availability. Using purposive sampling, the selection criteria for the study included respondents who must be within the fields of Arts, Media & Communication, Sales & Marketing, Design, Merchandising & Product Development. Data gathered using survey research questionnaires were organized through tabulations and subjected to content analysis, with frequency, percentage, rank and weighted mean as parameters. Results indicated that the experimental styles of fashion or the avant-garde are often seen and regarded as too trendy or unusual, though acceptable and still wearable as assessed by working women. However, majority of women or 58% failed to identify specific brands or store names specializing on upcycled clothes, though the eight percent difference between the values is minimal. Thus, this suggests that these women may not be fully aware of this concept. Unique designs were the respondents‟ primary concern for purchasing upcycled clothes and sustainability as the least. Majority of these women would prefer to purchase upcycled clothes made available as ready-to-wear than custom-made apparel because accessibility and convenience serve as important factors to be considered for their fast-paced and busy lifestyle. The researcher recommends that upcycled clothes could be further promoted for an overall consumer awareness on earth-friendly fashion with follow up studies on specific clothing attributes and modifications on research design and methods to further enrich this study.